Leadership Dynamics of Generations Y and Z from a Behavioral Theory Perspective - Hari Nugroho Akimas; Meiske Claudia (International Journal of Asian Business and Management, 2024)
This research aims to explore the leadership dynamics of generations Y (millennials) and Z (post-millennials) in an organizational context, using a qualitative approach. Generations Y and Z have taken center stage in modern management literature because of their unique characteristics that influence how they interact, adapt, and respond to leadership. This study uses qualitative methods to explore generations Y and Z's preferences for effective leadership styles. Research findings reveal that this generation tends to value flexibility in leadership style, which allows them to actively participate in decision making and put forward new ideas in a dynamic work environment. This research also highlights the importance of appropriate responses to rewards and recognition of the individual achievements of generations Y and Z. This research makes an important contribution to understanding how adaptive leadership practices influence the interactions and adaptation of generations Y and Z in the modern work environment. The managerial implications of this research include developing better leadership strategies to optimize the engagement and performance of generations Y and Z, as well as creating a work environment that supports growth and innovation in the long term